2020
DOI: 10.1111/disa.12424
|View full text |Cite
|
Sign up to set email alerts
|

Disaster risk reduction, community resilience, and policy effectiveness: the case of the Hazard Mitigation Grant Program in the United States

Abstract: Disasters triggered by natural hazards resulted in an accumulative economic loss of approximately USD 7 trillion and killed some eight million people worldwide in the twentieth century. Given the escalating threat posed by natural hazards to communities, scholars and practitioners are emphasising the importance of mitigation as a strategy to enhance community resilience. Little is known, though, about the extent to which governments' disaster risk reduction efforts have augmented community resilience outcomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 45 publications
(109 reference statements)
0
24
0
Order By: Relevance
“…The data that support the findings of the study are available from Lauren A. Clay Cutter, Burton, and Emrich, 2010;National Research Council, 2012;Ross, 2013;Ji and Lee, 2020;Shao et al, 2020). Second, counties are a key locus of local emergency management in the US (Wernstedt et al, 2019;Ji and Lee, 2020).…”
Section: Data Availability Statementmentioning
confidence: 58%
See 2 more Smart Citations
“…The data that support the findings of the study are available from Lauren A. Clay Cutter, Burton, and Emrich, 2010;National Research Council, 2012;Ross, 2013;Ji and Lee, 2020;Shao et al, 2020). Second, counties are a key locus of local emergency management in the US (Wernstedt et al, 2019;Ji and Lee, 2020).…”
Section: Data Availability Statementmentioning
confidence: 58%
“…Communities are delineated as counties for three reasons. First, it is in keeping with key research on community disaster resilience (see, for example, Cutter, Burton, and Emrich, 2010; National Research Council, 2012; Ross, 2013; Ji and Lee, 2020; Shao et al, 2020). Second, counties are a key locus of local emergency management in the US (Wernstedt et al, 2019; Ji and Lee, 2020).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…To explore the effectiveness of government mitigation policies on community resilience, Ji and Lee compared disaster loss data in counties receiving the Hazard Mitigation Grant Program (HMGP) in the United States. The results showed that counties that participated in HMGP were less likely to suffer property damage in future disasters [84].…”
Section: Research Hotspots Of Community Resiliencementioning
confidence: 97%
“…Connecting residents to federal funding, however, requires support from local and state level agencies (Ji and Lee 2021). Their roles in this process are described brie y below:…”
Section: Hmgp Participation and Trustmentioning
confidence: 99%